ANALISIS FAKTOR PENENTU STRUKTUR MODAL PERBANKAN DI INDONESIA - Eleonora Sofilda; Maryani , (Media Riset Akuntansi, Auditing & Informasi, 2007)
The objective of this paper is to analyze the determinant factors of capital structure in banking sector in Indonesia. The object of this paper includes 19 banks that have been listed in Jakarta Stock Exchange. There are 5 variables, choosed as the measurement of capital structure, those are: Size, Tangibility Non Debt Tax Shiekls, ProNabiNy and Depre-ciation. Data analysis used in this paper is the financial statement of each bank and taken from their balance sheet. The data period started from year 2003 until year 2005. This paper finds that all independent variables affect dependent variable (capital structure) simultaneously and partially. Independent variable size Kt tangibility (X2), NDTS (X), and depreciation variable (X5) have insignificant effect to capital structure. Meanwhile, profitabil-ity variable (X.) has significant effect to capita/ structure.Keywords: Capital Structure, Banking Industry